Prevalence of Cryptosporidium infection in domestic cats from an urban area in Brazil - da Silveira Neto, Luiz; Widmer, Giovanni; de Lima, Valéria Marçal Felix [UNESP]; Meireles, Marcelo Vasconcelos [UNESP]; Inácio, Sandra Valéria [UNESP]; Marques, Marcel Gambin; Marques, Ana Elisa Gregui Watanabe [UNESP]; de Matos, Lucas Vinícius Shigaki; da Cruz Panegossi, Mariele Fernanda; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2020)
We investigated the occurrence of Cryptosporidium oocysts shedding by domestic cats in an urban setting. The calculation of minimum sample size was based on an estimated prevalence of 10%, 5% absolute sampling error and a 5% significance level, resulting in 138 cats. A total of 612 owners of 2,290 cats had to be contacted for achieving the minimal sample size. In the end, only 55 owners accepted to participate in this investigation. Stool samples collected from 138 dogs were examined by microscopy using modified Kinyoun acid-fast staining, capture ELISA and nested-PCR followed by sequencing. Samples were considered positive when Cryptosporidium were detected by at least two diagnostic methods. Thirteen samples were positive (9.4%; 95% CI: 4.5 - 14.3). Cryptosporidium amplicons from seven out of the 13 samples were successfully sequenced and shared 99% genetic similarity to Cryptosporidium felis, GenBank access AF112575.1 was found. We concluded that Cryptosporidium infection is common in domestic cats from urban area and veterinary practitioners should guide cat owners to adopt preventive measures against the parasite to reduce the chance of infection in cats and householders.
Prevalência de infecção por Cryptosporidium em gatos domiciliados em uma área urbana no Brasil
Keywords: Cryptosporidiosis; Epidemiology; Feline; Prevalence; Public Health